ANALISIS KEMAMPUAN PENGUASAAN KOSAKATA BAHASA ARAB MELALUI BUKU â€œBELAJAR CEPAT TATA BAHASA ARAB â€œ DI UIN SULTHAN TAHA SAIFUDIN JAMBI - Ismail Fahri; Sri Sudiarti (Nazharat: Jurnal Kebudayaan, 2023)
The purpose of this research is to find out and uncover, 1) Implementation of the Arabic Learning process in the Arabic language and literature department of UIN Sulthan Thaha Saifuddin Jambi, 2) the steps of teaching Arabic by the Arabic language lecturers through the book Al-Qawaid al-Arabiyah al-Muyassarah ", 3 ) the level of mastery of Arabic vocabulary in Arabic language and literature students at UIN Sulthan Thaha Saifuddin Jambi, 4) the weaknesses and strengths of al-Qawaid al-Arabiyah al-Muyassarah books â€. in learning Arabic at UIN STS JambiThis research design uses a qualitative research approach, the target or respondents of this study are students majoring in Arabic and Arabic who are studying Arabic semester one. Data collection techniques through questionnaires in the form of quizzes that are open and closed, and also interviews. Data analysis was carried out qualitatively by producing data through analytical techniques suggested by Miles and Huberman, which was done in steps 1) data reduction, 2) data presentation, 3) conclusion drawing.The results of this study can be seen 1) the Arabic learning process at UIN STS Jambi uses a grammatical-translation approach, namely lecturers teaching qawaid, without honing skills such as kalam, qiraah and kitabah, 2) there is progress in mastering Arabic vocabulary, after it is applied al-qawaid al-arabiyah al-muyassarah book, many students have Arabic vocabulary because the book uses Arabic in total, and also the package book gives training on developing the abilities of istima ', kalam, qiraah, and kitabah.